Novel and Highly Sensitive Fluorescent Assay for Leucine Aminopeptidases - Huang, Huazhang (2009)
L-Leucine aminopeptidases (LAPs) are implicated in the progress of many pathological disorders, and play some regulatory roles in tumor cell proliferation, invasion and/or angiogenesis. Thus, LAPs could become not only new diagnostic or prognostic biomarkers, but also have potential as novel molecular targets for the treatment of several cancers. Highly sensitive assays are critical for early detection of changes in LAP activity and for screening potent LAP inhibitors. In this study, we developed a novel and highly sensitive fluorescent assay for LAPs based on substituted aminopyridines as fluorescent reporters. This assay was at least 100 and 20 fold more sensitive than commercial colorimetric or fluorescent LAP substrates, respectively. We also showed that this assay was a useful tool to monitor LAP activities in extracts from cancer cell lines, as well as for the high throughput screening of inhibitors, which could lead to new cancer treatments.